Sows' parity and coconut oil postnatal supplement on piglets performance - Santos, Luan S. [UNESP]; Caldara, Fabiana R.; Machado, Sivanilza T.; Naeaes, Irenilza A.; Foppa, Luciana; Garcia, Rodrigo G.; Moura, Rafael; Machado, Simone P. (Univ Cordoba, 2015)
Objectives. The study aimed to evaluate the effect of sows' of different parities and the supplement of coconut oil for piglets, on the development of litter. Materials and methods. A total of 51 sows of different parities and their 642 piglets were used in the trial. Each piglet was weighed and identified at birth in a sequential order. They were randomly distributed in two treatments (CG=control group and TG=test group). TG piglets had the first access to a dosage of 3.0 ml of coconut oil 12 hours after birth, and the second at 36 h after the first. Piglets were weighed at 21 days. In order to analyze the effect of the coconut oil supplement as a function of the weight at birth, piglets were grouped according to their weight (0.600 to 0.900 kg; 1.000 to 1.499kg; 1.500 to 1.999 kg; and 2.000 to 2.499 kg). Results. Sows parity affected the number and weight of born piglets. Sows in 4th, 5th and 7th parity had a larger litter than those from the 2nd parity. Sows from 2nd and 3rd parity had a lower number of piglets but heavier litter. No effect of the coconut oil supplement on neonatal piglets' performance was found. Conclusions. The coconut meal was neither beneficial to neonatal piglets nor to those with low weight at birth, which usually present low body energy.
Keywords: Energy sources; fatty acids; litter size; newborn animal